ANALISIS DAN PEMETAAN KERUSAKAN JALAN DENGAN METODE SURFACE DISTRESS INDEX PADA RUAS JALAN RAYA KEBONAGUNG - JALAN RAYA PEPEN KABUPATEN MALANG - Achmad Chullbuddin Badghey; Hendrata Wibisana (LPPM Universitas Abdurrab, 2024)
The increasing population and resulting increase in traffic volume can affect the condition of road surface construction, in this case causing a decline in the quality of the city's roads. The Kebonagung Highway - Pepen, is the main road that has experienced a decline in road quality. Based on observations, the SDI (surface distress index) method is good for determining road surface conditions on the Kebonagung - Pepen highway and mapping using SIG. The types of damage found at the research location include checkerboard cracks, longitudinal cracks, crocodile skin cracks, edge cracks, holes, wheel marks (grooves), patch damage, fall damage, and subsidence damage. The percentage results of road damage values based on the SDI method for the area of damage were 1.66% square cracks, 2.81% longitudinal cracks, 3.14% crocodile skin cracks, 2.27% edge cracks, 0.23% holes, 2 .87% wheel marks (grooves), 2.03% patch damage, 3.65% fall damage, and 0.22% sink damage. The condition value using the method on the Jalan Raya Kebonagung - Jalan Raya Pepen section shows good condition at STA 0+000 - 8+100 because it produces an SDI value (<50). From the results obtained all damage values ​​were based on the SDI method. Geographic Information System was implemented, namely creating a thematic map of road damage values on the Kebonagung Highway - Jalan Raya Pepen section.